Social media and women mobilization for community development - Ahmad, Sharu Aisha; Joseph, Ayodele B. (Yayasan Mitra Persada Nusantara, 2023)
The study explored the potential of social media for women mobilization to attain community development. Social media has become a very powerful platform that informs and educates its users. Community development is the advancement and progress of a particular community. Women play a vital role in community development. The study seeks to know the effects of social media in mobilizing women as well as examining how social media can help in women empowerment for community development. For the purpose of this study, the Diffusion of Innovation theory was employed to further expatiate the impact of social media for community development. Conclusively, it can be seen as though social media is very essential in mobilizing women for community development. Social media plays a vital role in enhancing community development. However, government should support programs that empower women. It is recommended that Development Agencies and State Ministry of Women Affairs should increase advocacy visits to women in the communities.